OVERCOMING LANGUAGE BARRIERS IN COMMUNICATION - Ahmedova Matluba Ibragimjonovna; Olimjonova Muxlisa Muxammadsalim qizi (TADQIQOTLAR.UZ, 2024)
Annotation: This article explores the causes of language barriers on effective communication. It discusses the challenges and misunderstandings that can arise when individuals do not share a common language, and ways in which these barriers can be overcome.